(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
The shift in educational orientation represents a critical issue as it directly relates to the fundamental function of educational institutions and the quality of their outputs. This transformation has reshaped various aspects of education, including curriculum design, educational objectives, learning processes, and evaluation systems, driven by globalization, rapid technological advancement, economic pressures, and labor market demands. This study aims to examine the forms of educational orientation shifts, the contributing factors, their impacts, and the reorientation efforts undertaken by educational institutions. Employing a descriptive qualitative approach through a literature review, data were collected from academic sources such as books, peer-reviewed journals, scholarly articles, and relevant electronic media. The findings reveal that educational orientation shifts in Indonesia are evident and largely influenced by globalization, technological progress, economic demands, and workforce requirements, resulting in weakened moral development, the reduction of spiritual values in the curriculum, and dilemmas faced by Islamic educational institutions. Consequently, reorientation efforts are necessary, emphasizing the integration of moral values with professional competencies, the reinforcement of a holistic vision of Islamic education, and the strategic role of educators and educational institutions.